A construção de redes sociais no processo de formação docente em Metaverso, no contexto do Programa Loyola - Locatelli, Ederson Luiz (Universidade do Vale do Rio dos Sinos, 2010)
The term "network" has been used by different fields of knowledge. In the scientific community, the term network was first used by the mathematician Leonard Euler in 1736 in Königsberg. Also, the term has been used in biology, in physics, Administration and Social Sciences, where this work will rely on to speak of social networks. However, this paper aims to discuss social networking in Education. In the experience I have developed with the Jesuit schools in Brazil, I noticed that the geographical distance between the schools, becomes a factor limiting the development of a collaborative, networked, nationwide. However, current digital technologies, including virtual learning environments, Web 2.0, virtual worlds in three dimensions, among others... may help overcome this limit, allowing the construction of a way to work collaboratively on common projects. It is from this premise that comes the main problem of this dissertation, which is to investigate how to configure the processes are enhanced and continued training, networking, the provision of ECODI, permeated by the Ignatian Pedagogical Paradigm (Context-ExperienceReflection-Action-Assessment), under the Schools Program through the Programa Loyola? The main problem, derive the following objectives: to involve the knowledge that teachers have in relation to Ignatian Pedagogy, how to work with Ignation Pedagogy into ECODIS and if the work in this environment is a way to promote networking among teachers. Moreover, it will seek to verify that this work can generate a closer contact between teachers and the digital generation. The scientific method used in this research was a qualitative-quantitative approach to quality by setting up an exploratory manner, using the technical procedures of the case study and classified as a documentary and bibliographical research. Furthermore, we used a content analysis applied to analyze the images and chats in the course ECODI Ignatian. With this, the survey showed that teachers who attended the course has a satisfactory understanding regarding the Ignatian Pedagogy and with that, get to work on the theme ECODIS in connecting themes. Also, after learning how to use the Metaverse, they feel very comfortable working together, overcoming the limitation is that the geographical distance. In addition, a major goal of teachers doing the course is the search for new ways of teaching and learning to work with the generation homo zapiens.
Keywords: Redes sociais; Pedagogia inaciana; Metaverso; Educação a distância; Formação docente; Social networks; Ignatian pedagogy; Metaverse; Distance education; Teacher training; ACCNPQ::Ciências Humanas::Educação